THE RELATION BETWEEN SCHOOL SUCCESS AND SELFEFFICIENCY WITH IN THE ADOLESCENTS - Nuredin, Mensur; Alili, Zumera (International Scientific Journal Vision, 2024)
This scientific study was conducted in two educational institutions: the private Islamic religious high school ("Isa Beu" - extended girls class in Gostivar) and the state medical high school, primarily attended by female students. The student cohort ranged in age from 15 to 18, spanning from the first to the fourth year, with class sizes of approximately 15 students in both the private and state schools, totaling 120 students. The primary objectives of this research were to investigate the impact of self-efficacy on students' academic performance, discern potential variances in self-efficacy between general and religious educational settings, explore the influence of residence on adolescents' self-efficacy, compare self-efficacy levels between rural and urban student populations, assess differences in self-efficacy based on socioeconomic status among adolescents, and examine the relationship between parents' social status and adolescents' self-efficacy.